Treadwell Gold : An Alaska Saga of Riches and Ruin - Kelly, Sheila, 1942- (Book collections on Project MUSE., 2010)
A century ago, Treadwell, Alaska, was a featured stop on steamship cruises, a rich, up-to-date town that was the most prominent and proud in all Alaska. Its wealth, however, was founded on the remarkably productive gold mines on Douglas Island, and when those caved in and flooded in the early decades of the twentieth century, Treadwell sank into relative obscurity. Treadwell Gold presents first-person accounts from the sons and daughters of the miners, machinists, hoist operators, and superintendents who together dug and blasted the gold that made Treadwell rich. Alongside these stories are vi.